6 arguments between a man and a woman (Journal of Parents and Teachers, 2026)
Jesús Garrido studies how conflicts between couples harbour deep emotional tensions. Using the parent-adult-child (PAC) model, the author explains that anger arises when the responses between the two are not parallel, but intersect. He shows various examples in which internal and power imbalances can be observed, depending on the role you adopt, generating struggles for authority or dependence as the solution. To this end, mature communication, which helps to avoid conflicts and resolve this situation, proposes identifying the roles that each person adopts in order to maintain emotional balance.
Keywords: Couple, Conflict, Communication and Roles.